A longitudinal PRINTO study on growth and puberty in juvenile systemic lupus erythematosus. Issue 4 (13th October 2011) - Rygg, Marite; Pistorio, Angela; Ravelli, Angelo; Maghnie, Mohamad; Di Iorgi, Natascia; Bader-Meunier, Brigitte; Da Silva, Carlos; Roldan-Molina, Rosa; Barash, Judith; Dracou, Cristina; Laloum, Sylvie Gandon; Jarosova, Katerina; et al.
Abstract : Objective: To obtain longitudinal data on growth/puberty in a large-scale, multi-national prospective cohort of juvenile systemic lupus erythematosus (SLE). Methods: Data from 331/557 (59.4%) patients ≤18 years old with juvenile SLE in active phase, with anthropometric data available at four follow-up visits, were studied. Results: There was a significant reduction in parent-adjusted height z score with time in females and males (p<0.0001), with a significant gender difference (p<0.0001) and with male height being most affected. Median body mass index z score peaked at 6 months and was still significantly above baseline after 26 months (p<0.01), with no gender difference. Standardised height reduction was inversely related to age at onset. Females with onset age <12 years had a median parent-adjusted height z score of −0.87 with no catch-up growth. At the end of the study, growth failure was seen in 14.7% of the females and 24.5% of the males. Height deflection (less than −0.25/year) was found in 20.7% of the females and 45.5% of the males. Delayed pubertal onset was seen in 15.3% and 24% of the females and males, respectively, and delayed/absent menarche was seen in 21.9%, while 36.1% of the females and 44% of the males had some degree of delayed pubertal development. Growth failure baseline determinants were previous growth failure (OR: 56.6), age at first visit ≤13.4 years (OR: 4.2) and cumulative steroid dose >426 mg/kg (OR: 3.6). Conclusions: The children at risk of having a negative effect on height and pubertal development are prepubertal and peripubertal children treated with >400 mg/kg cumulative dose of corticosteroids.